6. New Perspectives in Developing Teachers' Social-Emotional Skills to Prevent Bullying: The Role of Forum Theatre - Grădinariu Tudoriţa; Diac Georgeta (Sciendo, 2023)
The present study is in line with the concern for the prevention of bullying behaviors, which have been continuously and unprecedentedly expanding at national and European level. In this case, the socio-emotional competence of teachers is important. A solution for training and developing this competence is offered by continuing vocational training programs regulated at national and European level. In line with the recommendations of the Council of Europe (2018), which refer to complementing academic training with social, emotional and arts learning, our approach is intended as a reflection of the importance of an innovative interdisciplinary perspective in developing social-emotional competences in teachers by considering the theatrical technique Theatre Forum for effective bullying prevention. In this respect, we propose some directions for analysis: